The Impact of Internet Subsidies in Public Schools - Goolsbee, Austan; Guryan, Jonathan (The Review of Economics and Statistics, 2006)
In an effort to alleviate the perceived growth of a digital divide, the U.S. government enacted a major subsidy for Internet and communications investment in schools starting in 1998. In this paper, we evaluate the effect of the subsidy—known as the E-Rate—on Internet investment in California public schools. The program subsidized spending by 20%–90%, depending on school characteristics. Using new data on school technology usage in every school in California from 1996 to 2000 as well as application data from the E-Rate program, the results indicate that the subsidy did succeed in significantly increasing Internet investment. The implied first-dollar price elasticity of demand for Internet investment is between −0.4 and −1.1 and the greatest sensitivity is seen among urban schools and schools with large black and Hispanic student populations. Rural and predominantly white and Asian schools show much less sensitivity. Overall, by the final year of the sample, there were approximately 68% more Internet-connected classrooms per teacher than there would have been without the subsidy. Using a variety of test score results, however, we do not find significant effects of the E-Rate program, at least so far, on student performance.